The Right to Water in the Case-Law of the Inter-American Court of Human Rights (2014)
The human right to water is nowadays more broadly recognised, mainly due to the essential societal function that this resource plays; likewise, because of the present water scarcity is generating conflicts between its different uses. Thus, this right aims at protecting human beings by guaranteeing access to clean water that is essential to satisfy vital human needs. Similarly, access to clean water is an important element to guarantee other rights including the right to life and health. The recognition of the right to water is mainly achieved in two ways: as a new and independent right and as a subordinate or derivative right. Concerning the latter, the right to water can emanate from civil and political rights, such as the right to life; or can be derived from economic, social and cultural rights, including the right to health, the right to an adequate standard of living, and the right to housing. This contribution explores the position of the Inter-American Court of Human Rights regarding the right to water, and analyses whether the Court has recognised the right to water and, if so, in which manner.